Analisis Kesulitan Pemahaman Konseptual Siswa Dalam Menyelesaikan Soal Pada Materi Fisika di XI MIA 3 DI MAN 2 Langsa - Armelia Yuniani; Mutia Rahmatika; Kastari Kastari; Muhammad Ichsan; Nurmasyitah Nurmasyitah (Program Studi Pendidikan Fisika FKIP Universitas Samudra, 2020)
The research aims to determine the level of difficulty and differentiation of the exam on the middle semester of the subjects of the Physics class XI MIA 3 in MAN 2 Langsa. The research method used is a descriptive quantitative method. The results showed that for the difficulty level was obtained 13 questions (43.33%) Easy, 17 questions (56.66%) Medium and 0 problem (0%) Difficult. The results of the analysis of the differentiator power about 10 questions (33.33%) Received, 16 questions (53.33%) Discarded and 4 questions (13.33%) Fixed. Overall about the middle semester exam of physics subjects in class XI MIA 3 in MAN 2 Langsa year 2018/2019 is categorized as a good question, because it has the largest percentage of difficulty level in the category of moderate problems, namely as many as 17 questions (56.66%) And the largest percentage of the differentiator's power in the category of questions received 10 questions (33.33%).